Visões de arte e moda feminina na Amazônia: a coleção do Museu Dica Frazão - (:unkn) unknown (Universidade Federal do Oeste do Pará, 2023)
This paper studies the collection of the Dica Frazão Art Museum, which for two decades has had a long-term exhibition of textiles made from plant fibers. The garments, which are the main artifacts in this museum collection, are at the center of the research because, through them and knowledge of fashion, it is possible to understand how these objects contribute to individual and social memory in Santarém, as well as bringing to light visions of women's art and fashion in the mid-1950s to 1998. The categories Museum, Collection and Fashion will be worked on in order to understand the symbolic value of these objects in close relation to the trajectory of the craftswoman herself. We established theoretical dialogues with reference studies in the field and research into a body of documentation found in the Museum, in photographs, in news published between the 1970s and 1980s, and in interviews granted by Dica Frazão herself. The research takes into account the possible strategies of symbolic valorization of the artist, who evokes repertoires such as pioneering spirit, authenticity and identity with Amazonian biodiversity.
Keywords: COLEÇÃO; ARTE; MODA; MUSEU; DICA FRAZÃO; INDUMENTÁRIA; CNPQ::CIÊNCIAS HUMANAS